Some reproductive biology aspects of bonylip barb (Osteochilus vittatus Valenciennes, 1842) in the waters of Benanga Reservoir, East Kalimantan - Jusmaldi Jusmaldi; Nova Hariani; Medi Hendra; Nikmahtulhaniah Ayu Wulandari; Sarah Sarah (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2020)
Bonylip barb (Osteochilus vittatus Valenciennes, 1842) that belongs to the Cyprinidae family is one of the native freshwater fishes in Indonesian waters. Currently, status of this species in Benanga Reservoir, East Kalimantan is in over-exploited. Fish resources management, therefore, is needed to maintained fish stock in the reservoir based on fish reproductive biology aspects. The purpose of this study was to analyze some aspects of the reproductive biology including sex-ratio, gonad maturity, length at first gonad maturity, spawning season, fecundity, and spawning patterns as basic information for its management. Fish collection was carried out monthly on the third week from January to May 2019 at three stations. The fish samples were captured by using experimental gill nets with mesh size of 1; 1.5; 2; and 3 inches. A total of 278 bonylip barb was caught, consist of 92 males and 186 females. Sex ratio of male and female in the gonad mature stage was 1: 2.4. The average length at first gonad maturity in male and female were 136.08 mm and 137.38 mm, respectively. Peak of spawning occurs during the rainy season in May, with more than 90% of fish in mature stage with GSI in male and female were 6.88%, 13.16% respectively. Total fecundity ranged from 7312-22923 eggs individual-1 and egg diameter ranged from 0.6-1.94 mm. According to distribution of egg diameter, bonylip barb was categoried as a total spawner. Some management strategies that can be carried out are using fishing gears with mesh size above 2 inches, limiting fishing activities in the peak of the spawning season, prohibiting fishing gear using electric shocker and protection the reservoir from erosion. Abstrak Ikan nilem (Osteochilus vittatus Valenciennes, 1842) merupakan jenis ikan air tawar famili Cyprinidae asli perairan Indonesia. Saat ini, ikan nilem di perairan Waduk Benanga Kalimantan timur telah diekploitasi lebih. Karena itu diperlukan pengelolaan di alam agar stok ikan tersebut tetap terjaga; dengan melakukan kajian aspek biologi repro-duksi. Tujuan penelitian ini adalah menganalisis aspek biologi reproduksi mencakup nisbah kelamin, kematangan gonad berkaitan dengan musim, ukuran ikan kali pertama matang gonad, musim pemijahan, fekunditas dan tipe pemijahan sebagai informasi dasar dalam pengelolaannya. Penangkapan ikan dilakukan selama 5 bulan, dari Januari hingga Mei 2019 dan dilaksanakan pada minggu ketiga setiap bulannya di tiga stasiun. Contoh ikan ditangkap dengan menggunakan jaring insang eksperimental berukuran mata jaring 1; 1,5; 2; dan 3 inci. Jumlah total ikan nilem yang tertangkap 278 ekor terdiri atas 92 jantan dan 186 betina. Nisbah kelamin ikan jantan dan betina pada tahap matang gonad 1: 2,4. Panjang kali pertama matang gonad pada jantan rata-rata 136,08 mm dan betina rata-rata 137,38 mm. Puncak pemijahan terjadi saat musim penghujan di bulan Mei dengan nilai persentase TKG IV >90%, IKG jantan 6,88% dan IKG betina 13,16%. Fekunditas total berkisar 7312-22.923 butir individu-1 dan diameter telur berkisar 0,6-1,94 mm. Sebaran diameter telur menunjukkan pola pemijahan serempak. Strategi pengelolaan yang disarankan adalah penggunaan ukuran mata jaring di atas 2 inci, pembatasan penangkapan ikan pada puncak pemijahan pada bulan Mei, pelarangan alat tangkap menggunakan listrik dan perlindungan Waduk Benanga dari erosi